(untitled) (Conferencea, 2022)
Cooperation in the fields of trade, finance and security in the Asian region was carried out mainly on the basis of bilateral agreements during the post-war period. Since 2010, significant progress has been made through multilateral cooperation. As a result of the effective operation of a number of regional organizations, multilateral functions have been significantly improved. This article examines Japan’s pursuit of multilateralism in its foreign policy toward Asia as a strategy to realize the country’s interests and highlights the need for Japan to intensify its coalition-building efforts as part of its Asian policy.